Pengaruh Model Pembelajaran Think Pair Share (TPS) terhadap Hasil Belajar Bahasa Inggris Kelas V SD Negeri WIOI - Non Norma Monigir; Lady Carolina Pangalo; Virginia Anastasya Tuwaidan (Departement of Mathematics Education, 2024)
This study uses materials on Public Space and Describing People to test how the Think Pair Share (TPS) learning paradigm affects the English learning outcomes of fifth-grade students at Wioi Elementary School. Quantitative research using an experimental design is the methodology used. Thirty students were selected intentionally to be the research sample. A learning outcome test that assesses the understanding and application of vocabulary and sentence structure in the material being taught was used as an instrument. To find out whether there was a significant change in learning outcomes before and after the TPS model was applied, the test result data was evaluated using the t-test in SPSS. There was a significant difference between learning outcomes before and after the TPS model was used, according to the results of the SPSS analysis which showed a significance value (p-value) of 0.000, which is smaller than the significance level of 0.05. This shows how the TPS learning paradigm can improve students' English learning outcomes, especially those related to vocabulary understanding and speaking skills. As a result, the think-pair-share approach works well to improve students' learning outcomes in terms of character description and public space.